Let’s talk about emotional labor: some reflections from the field - Keller, Judith; Pierce, Colt (Journal of geography in higher education, 2023)
While methodologies on fieldwork are widely discussed in geography, this paper illuminates the challenges of emotional labor that are associated with ethnographic fieldwork. For many geographers, fieldwork is an exciting and crucial part of their job, but for some, especially junior faculty and graduate students, there are many undiscussed and unanticipated difficulties associated with this work. We focus on three challenges that in particular require emotional labor: always being on alert, attachment to places, and the relationships to research participants. Building on personal stories from their research in US cities, both authors reveal the hardships and realities of ethnographic fieldwork. Yet, in order to open up more critical dialogue and honest conversations about the emotional toll of research, this paper demands an institutionalization of support services, particularly for Early Career Researchers (ECRs), so fieldwork can continue to be a crucial and rewarding part of our discipline.
Online veröffentlicht: 11. Oktober 2023
Gesehen am 20.12.2023